2009
DOI: 10.1159/000228541
|View full text |Cite
|
Sign up to set email alerts
|

Strict Volume Control and Longitudinal Changes in Cardiac Biomarker Levels in Hemodialysis Patients

Abstract: Background: Our aim was to analyze the longitudinal changes in cardiac biomarker levels in hemodialysis patients with high comorbidity treated in our special hospital unit. We hypothesize that strict volume control strategy (salt-restricted diet, extended dialysis sessions and dry weight clinical assessment and reassessment in every session) could prevent progression of left-ventricular damage and, therefore, progressive increment in cardiac biomarker levels over time. Methods: This is a longitudinal cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…An increase in BNP concentration over time in dialysis patients has been previously demonstrated for both NT-BNP-76 (7,14,15) and BNP-32 (16), although two other studies demonstrated no significant change in these markers (17,18). The concurrent measurement of both forms of BNP in three groups of patients allowed us to directly compare patients with CKD 3-4 and KTRs to dialysis patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An increase in BNP concentration over time in dialysis patients has been previously demonstrated for both NT-BNP-76 (7,14,15) and BNP-32 (16), although two other studies demonstrated no significant change in these markers (17,18). The concurrent measurement of both forms of BNP in three groups of patients allowed us to directly compare patients with CKD 3-4 and KTRs to dialysis patients.…”
Section: Discussionmentioning
confidence: 91%
“…All samples in this study were collected just before the hemodialysis procedure to eliminate effects of this procedure (19,20). Studies of the effect of vascular access creation on BNP concentrations are inconclusive (21,22), and studies of BNP as a biomarker of volume overload in patients receiving dialysis also vary in their conclusions (15,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been observed that CKD patients with high troponin T concentrations had clear evidence of myocardial dysfunction and raised left ventricular filling pressure (Sharma et al, 2006), supporting that volume and pressure overload can cause excessive ventricular wall tension with resultant myofibrillary damage or cardiomyocites death (Horwich TB et al, 2003). In this way, a strong association between troponin T and NTproBNP has been observed in hemodialysis patients (figure 4) (Ortega et al, 2009) and both troponin T and NT-proBNP levels has been observed to be higher in volume-overloaded CKD patients (Sommerer et al, 2007). Thus, it seems that the increased troponin T in a high proportion of patients with CKD could be related to myocardial injury induced by an increased left ventricular volume especially in those patients with diastolic dysfunction, in whom a small increase in end-diastolic volume produces an exaggerated increment in end-diastolic pressure with the subsequent myocardial damage.…”
Section: Other Cardiac Biomarkers: Troponin Tmentioning
confidence: 84%
“…Thus, these results suggest that diastolic dysfunction progress over time among patients with chronic kidney disease. In another longitudinal study performed in hemodialysis patients (Ortega et al, 2009), the effect of strict volume control on the evolution of cardiac biomarker levels over time was analyzed. In this study, the strategy of strict volume control permitted the stabilization of cardiac biomarker levels over time, suggesting that this strategy may prevent further progression of left ventricular hypertrophy, cardiac fibrosis and diastolic dysfunction.…”
Section: Association Between Inflammation Overhydratacion and Cardiamentioning
confidence: 99%
See 1 more Smart Citation